2017
DOI: 10.1111/hex.12661
|View full text |Cite
|
Sign up to set email alerts
|

A patient decision aid for risk‐reducing surgery in premenopausal BRCA1/2 mutation carriers: Development process and pilot testing

Abstract: Background BRCA1/2 mutation carriers’ choice between risk‐reducing salpingo‐oophorectomy (RRSO) and salpingectomy with delayed oophorectomy is very complex. Aim was to develop a patient decision aid that combines evidence with patient preferences to facilitate decision making.DesignSystematic development of a patient decision aid in an iterative process of prototype development, alpha testing by patients and clinicians and revisions using International Patient Decision Aid Standards (IPDAS) quality criteria. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 33 publications
0
36
0
12
Order By: Relevance
“…To date, there is a lack of patient‐directed guidance to mitigate challenges to communicating genetic risk to relatives. High‐quality patient decision support techniques present an opportunity to enhance shared decision making and supplement genetic counselling sessions, but do not yet exist for the purposes of enhancing interfamilial communication about hereditary cancers 23,24 . Decision support techniques have been shown to increase patient‐physician communication; promote accurate knowledge; clarify values; resolve decisional conflict; and increase decisional satisfaction 25‐31 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is a lack of patient‐directed guidance to mitigate challenges to communicating genetic risk to relatives. High‐quality patient decision support techniques present an opportunity to enhance shared decision making and supplement genetic counselling sessions, but do not yet exist for the purposes of enhancing interfamilial communication about hereditary cancers 23,24 . Decision support techniques have been shown to increase patient‐physician communication; promote accurate knowledge; clarify values; resolve decisional conflict; and increase decisional satisfaction 25‐31 .…”
Section: Introductionmentioning
confidence: 99%
“…Ten DAs are described in primary studies and were found in the database search 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 . Six of these were available as full version 28 , 29 , 32 , 33 , 34 , 35 . Four DAs were not available as full version as two authors could no longer access the DA 27 , 31 , the format of the DA was no longer in use 36 or our enquiry was not answered 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Nicht ausgewertet werden konnte die Information, auf welche Art und Weise die Frauen auf die EH zugreifen konnten, da es hierzu in mehreren EH bzw. in den dazugehörigen Studien keine klaren Angaben gab.InhaltInhaltlich können die EH in 3 Gruppen eingeteilt werden: 5 der 20 EH (25 %) beschreiben sowohl präventive Maßnahmen für BK als auch für EK[27,29,31,33,35], 9 (45 %) haben den Fokus auf präventiven BK-Maßnahmen[32,37,39,42,45,46], 6 (30 %) auf präventiven EK-Maßnahmen[34,38,40,41,43,44]. Eine weitergehende Analyse der Inhalte der EH konnte nur für die 16 EH erfolgen, die in Vollversion vorlagen.…”
unclassified
“…These DAs provide differentiated risk information for women with BRCA1 and BRCA2 mutations and address questions relating to dealing with both the BC risk and the OC risk. This represents an advantage compared to international DAs, which do not differentiate between BRCA1 and BRCA2 mutation carriers with and without a history of BC [ 72 , 73 ], which address a broader target group of women with an increased risk of BC and/or OC [ 59 – 61 , 64 , 74 , 75 ], and which primarily tackle either the risks of BC [ 59 , 64 ] or OC [ 60 , 63 , 74 – 76 ]. There are very few DAs specifically designed for women with BRCA1/2 mutations with a history of BC [ 77 ].…”
Section: Discussionmentioning
confidence: 99%